Pengembangan Nilai Agama dan Moral Anak Usia Dini Etnis Jawa dan Madura di Kabupaten Pasuruan - M Mujib Utsmani (SELING: Jurnal Program Studi PGRA, 2017)
The dialog of Javanese and Madurese in Pasuruan be interesting, because the two ethnic groups have a habit of instilling a strong tradition in relegiusitas in society. So that the two ethnic groups in Pasuruan showing positive value of diversity in society. The purpose of this research are to know the concept of the development of Value of Religious and Moral invested educators in delivering the students are able to think, act, and behave commendable (akhlaq al-karimah) on Ethnic Java-Madura in Pasuruan, to know the concept of educators aware of the importance of moral development and Religious Values ​​in children even more at an early age Ethnic Java-Madura in Pasuruan. This study want to understand the phenomenon of rational, interpretive, and evaluative. Giving meaning, interpretation, and meaning to the development of Religious and Moral Values ​​is viewed from a conceptual perspective, the changing character of education and paradigmatic theoretical perspective. Therefore, this study is a qualitative approach. Results from this study is that parents and early childhood teachers in Pasuruan district has shown a variety of methods and gives examples of concrete in the development of religious values ​​and morals to the students whose background Javanese and Madurese, although there are a few things in the study of developmental psychology child doing less precise. With the use of methods that are variations of the children also feel happy and cheerful in the learning process. Recommended to teachers who deal with early childhood in order to improve understanding more about the didactic-methodical, especially at the stage of early childhood development. In addition, in implanting and developing religious values ​​in early childhood fun ways to be further enhanced.